BUB1 promotes lung adenocarcinoma progression by regulating STAT3/GPX4-mediated ferroptosis - Mo, Xiaocong; Liu, Ying; Wang, Yu; Pan, Xiaofen; Zhu, Mengyuan; Liao, Jiehao; Liu, Minling; Li, Tingwei; Li, Xueying; Fang, Shuo; Wang, Bo (Frontiers in Oncology, 2026)
IntroductionLung adenocarcinoma (LUAD) is the leading cause of cancer-related mortality worldwide, but its therapeutic efficacy remains suboptimal. This study explores the functional role and underlying mechanism of BUB1 in LUAD.MethodsIn vitro, BUB1 knockdown (si-BUB1) in A549/H1299 cells was performed, and effects were assessed. The ferroptosis inhibitor Fer-1 was used. Mechanistically, the role of the STAT3/GPX4 axis was investigated through overexpression experiments. In vivo, xenograft models were used.ResultsBioinformatics analysis highlighted a significant upregulation of BUB1 in LUAD tissues, with elevated expression levels correlated with reduced disease-free survival (DFS) and overall survival (OS). BUB1 knockdown markedly suppressed cell proliferation, migration, and invasion, while concurrently inducing ferroptosis. This was evidenced by typical mitochondrial morphological changes (shrinkage, increased membrane density, reduced cristae), altered ferroptosis-related markers (decreased FTH1/SLC7A11, increased COX2), elevated Fe²+/MDA levels and reduced GSH activity, which could be reversed by Fer-1. BUB1 silencing suppressed the expression and phosphorylation of STAT3, thereby downregulating the transcription of GPX4. Overexpression of STAT3 and GPX4 partially reversed the inhibitory effects of BUB1 knockdown on LUAD cell malignancy and abrogated the ferroptosis induced by BUB1 silencing. In vivo, xenograft models further validated that BUB1 silencing significantly reduces tumor volume, accompanied by modulation of ferroptosis-related genes in tumor tissues.DiscussionCollectively, our findings identify BUB1 as a novel prognostic biomarker and therapeutic target for LUAD, revealing a new regulatory mechanism by which BUB1 promotes LUAD progression through the activation of the STAT3/GPX4 axis to suppress ferroptosis.